The Concept of Predestination and Free Will in Iqbal and Nursi - Mohamed, Yasien (Afkar: Jurnal Akidah dan Pemikiran Islam, 2006)
This paper deals with the concept of divine predestination (qadar) and human free will (iradah) as conceived by two modern Islamic thinkers,Muhammad Iqbal (1876-1938) and Said Nursi (1873-1960). The problem of free will and divine destiny has been a perennial dilemma for thinkers throughout the ages, and Iqbal and Nursi have attempted to address the problem in their own respective ways. Although Iqbal turned to modern philosophy for inspiration, his views on the matter are akin to those of the Qadirites and the Mu’tazilites. Nursi turned to Ash’arite Kalam to resolve the dilemma.